2019
DOI: 10.1186/s40494-019-0298-2
|View full text |Cite
|
Sign up to set email alerts
|

Archaeometric characterization of Byzantine pottery from Păcuiul lui Soare

Abstract: Archaeometric investigations using OM (optical microscopy) and micro-PIXE (particle induced X-ray emission) were performed on 45 ceramic shards unearthed in archaeological excavations at Păcuiul lui Soare (southeastern Romania) and dated to the eleventh century AD. This study aimed to get clues about the raw materials and manufacturing techniques used by the potters from the Lower Danube area during the Byzantine period. The analyzed ceramic fragments were selected according to stylistic and archaeological cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…The analyses did not reveal the presence of kaolin. White clay deposits, sometimes with different shades of yellow, are known in several areas of Dobrudja, the closest to our discoveries are in Medgidia–Mircea Vodă, at approximately 30–40 km (Bugoi et al, 2019). It can be assumed the idea about the imported nature of raw material or pottery items from the center of Dobrudja.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…The analyses did not reveal the presence of kaolin. White clay deposits, sometimes with different shades of yellow, are known in several areas of Dobrudja, the closest to our discoveries are in Medgidia–Mircea Vodă, at approximately 30–40 km (Bugoi et al, 2019). It can be assumed the idea about the imported nature of raw material or pottery items from the center of Dobrudja.…”
Section: Discussionsupporting
confidence: 66%
“…This is corresponded to the lead oxide phase. Previously, it was assumed (Wiechert et al, 2005) that the PbO oxide is a component of the olive‐green color glaze, including used for decorating pottery (Bugoi et al, 2019) found in the Dobrudja region of Romania. The presence of lead oxide in the glaze was also found in ceramic fragments S_1, S_2, S_3, S_4, S_21, S_22, and S_23.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, archaeometric investigations of ceramics from Alcazar of Nájera (Spain) and Byzantine pottery from Păcuiul lui Soare (Romania) archaeological sites were performed by Calparsoro et al [24] and Bugoi et al [25] in trying to establish the provenance and/or the consumption and circulation of pottery in specific geographical regions and time periods.…”
mentioning
confidence: 99%